“Rancas will fight”: Subversion as a solution in Redoble por Rancas (1970) by Manuel Scorza - Valeria, Valeria (2023)
In this article we study the first novel of the Scorzian pentalogy. In this way, the project called La guerra silenciosa deals with the peasant struggles that took place in the central Andes of Peru, which have not been recorded by the official history of the country. In Redoble por Rancas (1970) we appreciate the tripartition of the prevailing power in the community, which affects the local peasants in disproportionate quantities. From these facts, we glimpse three subjects as the pioneers of the peasant organizations in Rancas: Espíritu Félix, Fortunato and Héctor Chacón. They managed to position themselves, from different perspectives, against the power in the area. These pioneers allow us to visualize the way in which power operates in the face of the people’s protest, but, above all, we observe the intention of the diegetic discourse by placing us in front of a desolate Andean panorama.